The biggest challenge in the fight against the COVID-19 pandemic: Vaccine hesitancy - Sirekbasan, Serhat (Ukrainian Journal of Nephrology and Dialysis, 2021)
I would like to mention an issue discussed constantly these days in the light of scientific data. It would be best to start by answering a question everyone is curious about before we start the main topic. Will this virus go away? The answer is simply “No”. The virus will probably continue to exist together with us; however, one day, the pandemic will end. The only answer we can give to the question of how this pandemic will end is “scientific and social fight”. All countries throughout the entire world are fighting to control the spread of SARS-CoV-2. The most important among these global fights is proper medical treatment in addition to an early, rapid and accurate diagnosis. Besides, another aspect that will crown this fight is the vaccination programs. The success of this fight depends on people’s accepting the vaccines. A total of 10 of the vaccine candidates, which numbered more than 165 developed within a record time period, have achieved approval after their final stages of effectiveness tests on a large scale as of March when the whole world mobilized to produce vaccines to stop the pandemic. Unfortunately; however, a vaccine against COVID-19 is unlikely to provide full protection. Also, even if a safe and effective vaccine comes to be known, it will not be possible to reach adequate distribution worldwide within a short time period. It is estimated that the time for the distribution of a safe and effective vaccine to the population will be between the end of 2020 and early 2022. However, even in the presence of adequate vaccines, vaccination of a sufficient number of population cannot be guaranteed due to hesitations, indecisiveness, and oppositions to the vaccine. Although vaccination is considered to be one of the most successful public health measures, an increasingly growing number of people perceive it as unsafe and unnecessary. The lack of trust in vaccines comes before us as a threat to the success of vaccination programs. Hesitation, indecision, and opposition to vaccines is an extremely important issue and requires to be dealt with. As a matter of fact, vaccines, which save approximately 2-3 million lives each year, are among the greatest achievements of the past two centuries. Vaccines, which eliminated the smallpox disease successfully, also reduced the prevalence of many important diseases greatly, such as polio and measles. Today, more than 30 infectious diseases can be controlled on a worldwide scale with the existing licensed vaccines; and it is prevented that the limited public healthcare resources are spent in vain by decreasing the burden of infectious diseases that are preventable with vaccines on the healthcare system. The way to eliminate the detrimental effects of this pandemic depends on the implementation of effective and safe vaccines as soon as possible, and on maintaining this at high rates. An overall “herd immunity”, which will be achieved with high vaccination rates, will also limit the ability of the virus to spread. Of course, how long the protective immunity to vaccines will last will determine our future regarding the virus; however, it must be kept in mind that the uncertainty we are experiencing now regarding the condition of the pandemic stems from our attitudes about vaccine rejection rather than the immune response. In conclusion, the potential of vaccines to prevent diseases and save lives has never been more remarkable throughout history. However, the magnitude of the hesitations regarding the vaccines was not at such dimensions. As misinformation about vaccines spreads, public confusion also increases, and various hesitations occur against the vaccine. These hesitations prevent the success of scientists and the attempts to spread the vaccine. Attention should be paid not to spread misguiding information regarding the safety and effectiveness of immunization, explanations that may be misunderstood of especially those who do not know about the subject should be prevented, and necessary information should be provided regularly regarding the concerns of the public. In any case, the potential benefit of the existing effective vaccines depends on the adequate acceptance of them by society. For this reason, the most important task that stands out before us is to raise public awareness by informing society to eliminate hesitations regarding the vaccines to increase vaccine adaptation rates in the entire population.